Self medication practice and associated factors among students of Asmara College of Health Sciences, Eritrea: a cross sectional study - Zenawi Zeramariam Araia; Nahom Kiros Gebregziabher; Araia Berhane Mesfun (Taylor & Francis Group, 2019)
Background Self-medication is a common practice globally and the resulting irrational drug use is raising concerns. Up-to-date there is no systematic study conducted on self medication practice among students or the general community in Eritrea. The present study aimed to determine the prevalence of self-medication practice and its influencing factors among students of Asmara College of Health Science. Methods A cross sectional study was conducted from 21st May -15th June 2018. Data on self medication practice and its associated factors was collected using a self-administered questionnaire. Data analysis was done using SPSS − 23 and explained with descriptive and inferential statistics. Results A total of 313 students responded to the questionnaire with a response rate of 93.6%. The overall prevalence of self-medication practice was 79.2%. Headache and fever were reported as the most common complaint related to self-medication practice. Among the reasons for self medication practice, prior experience was the most frequently reported. Analgesics, antipyretic and antibacterial were the leading class of medicine used in self-medication practice while adverse drug reactions were reported by 9.2% of respondents. In this study, sex, income, and school of study were found to be the independent predictors for self-medication practice. Conclusion National guideline on medicine access should be developed and strong measures should be implemented to halt the selling of medications without a proper prescription. In addition, students should be educated on the consequences of self-medication practices.